Effects of weight regain following intentional weight loss on glucoregulatory function in overweight and obese adults with pre-diabetes. Issue 3 (May 2015) - Beavers, Kristen M.; Case, L. Douglas; Blackwell, Caroline S.; Katula, Jeffery A.; Goff, David C.; Vitolins, Mara Z.
Summary Objective To assess the extent to which initial, intentional weight loss-associated improvements in glucose tolerance and insulin action are diminished with weight regain. Methods 138 overweight and obese (BMI: 32.4 ± 3.9 kg/m2), adults (59.0 ± 9.7 years), with pre-diabetes were followed through a 6-month weight loss intervention and subsequent 18-month weight maintenance period, or usual care control condition. Longitudinal change in weight (baseline, 6, 24 months) was used to classify individuals into weight pattern categories (Loser/Maintainer (LM), n= 50; Loser/Regainer (LR), n = 51; and Weight Stable (WS), n = 37). Fasting plasma glucose (FPG), insulin, and insulin resistance (HOMA-IR) were measured at baseline, 6, 12, 18 and 24 months and model adjusted changes, by weight pattern category, were assessed. Results LMs and LRs lost 8.3 ± 4.7 kg (8.7 ± 4.5%) and 9.6 ± 4.7 kg (10.2 ± 4.7%) during the first 6 months, respectively. LM continued to lose 1.1 ± 3.4 kg over the next 18 months (9.9 ± 6.5% reduction from baseline; p < 0.05), while LRs regained 6.5 ± 3.7 kg (3.3 ± 5.3% reduction from baseline; p < 0.05). Weight change was directly associated with change in all DM risk factors (all p < 0.01). Notably, despite an absolute reduction in body weight (from baseline to 24 months) achieved in the LR group, 24-month changes in FPG, insulin, and HOMA-IR did not differ between WS and LR groups. Conversely, LM saw sustained improvements in all measured DM risk factors. Conclusions Significant weight loss followed by weight loss maintenance is associated with sustained improvements in FPG, insulin, and HOMA-IR; conversely, even partial weight regain is associated with regression of initial improvements in these risk factors towards baseline values.